Polemik Amalan Lotus Birth dari Perspektif Hukum Islam: The Polemic of Lotus Birth Practice from Islamic Law Perspective - Kamaruddin, Nur Kamilah; Ramli, Mohd Anuar; Abdul Wahab, Raihana (Jurnal Fiqh, 2018)
Nowadays, there are various practices in society related to the birth process, including the management of the umbilical cord and the placenta. It involves the practice of religious teachings, local traditions, alternative medicine as well as modern medicine. Among the practices include the lotus birth, which is to keep the baby’s umbilical cord until it falls by itself. This practice poses a polemic between the medical experts and the lotus birth practitioners. In this regard, this study will discuss the practice of lotus birth, the views of medical experts and lotus birth practitioners as well as the analysis of the practice from the perspective of Islamic ruling. To achieve this objective, researchers used a qualitative approach, including both a library research and field research involving interviews with medical experts and lotus birth practitioners. The data collected was analysed inductively and comparatively. The findings show that the practice of lotus birth is contrary to Islamic ruling which is clearly stated that cutting of the umbilical cord is mandatory. In addition, the practice of lotus birth does not specifically benefit the baby and yet it exposes the baby and the mother to the risk of morbidity and mortality. In this regard, these pseudo-scientific practices should be abolished by mothers for the right of the child and the benefits of the newborn baby to receive the best treatment in line with the advancement of medical world.